THE CONTRIBUTION OF LENGKO-LENGKO GAME TO STUDENTS COLLABORATION IN ENGLISH CLASSROOM - Wirastin, Yulia; Rahmiatin, Titin; Nasrullah, Rahmat; Rusli, Tri Indah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Traditional games, as manifestations of cultural heritage, offer significant potential for creating dynamic and interactive learning environments. This study investigates the efficacy of the Lengko-Lengko traditional game as a pedagogical strategy for fostering student collaboration in an English as a Foreign Language (EFL) classroom. A descriptive qualitative methodology was employed, with data collected through in-depth classroom observations and video recordings of seventh-grade students at SMPN 20 Kendari. Data were analyzed thematically using the interactive model of Miles and Huberman. The findings demonstrate that the game significantly enhanced key facets of collaborative learning, evidenced by marked improvements in positive interdependence, individual accountability, promotive interaction, social skills, shared decision-making, equal participation, and conflict resolution. The game also served as a strong motivator, increasing students' willingness to use English; however, this use remained inconsistent and group reflection was identified as an area needing further development. This study concludes that the Lengko-Lengko game is not merely a recreational activity but a powerful, culturally grounded pedagogical tool. It effectively transforms the classroom into a collaborative community, bridging cultural preservation with modern educational objectives. The research provides educators with a practical framework for leveraging indigenous games to enhance 21st-century skills and enliven language learning.